ADAPTASI TEKNOLOGI 3D PRINTER SEBAGAI MEDIA PEMBELAJARAN MODERN BAGI GURU BIOLOGI DI KOTA PALOPO - Fitrah Al Anshori; Wahyu Hidayat; Wisnu Kurniadi (Jurnal Abdi Insani, 2023)
Learning media is a supporting component in the teaching process, especially biology. Learning media helps teachers explain material that is complicated and difficult to present in class. Many alternative learning media are available today, starting from original media which can come from the sea, forests, gardens and places around the school. Currently, there is modern technology, namely 3D printing. This technology is believed to be able to help teachers create biology learning media independently. The purpose of this activity is to share information about modern biology learning media that is based on 3D printing. This training activity method uses lecture techniques, and direct demonstrations. This activity began with observation, training in making 3D printing biological media, and training in implementing biological media in schools. The result of this activity was an increase in partners' knowledge about 3D printing machines from 12.5% to 87.5%. There was an increase in partners' knowledge of HKI management from 18.75% to 87.5%. There was an increase in partners' knowledge of 3D printing media models from 6.25% to 93.75%. There was an increase in partners' knowledge about cura ultimaker material 0% to 81.25%. There was an increase in partners' knowledge of media coloring techniques from 37.5% to 100%. The conclusion from this activity is that based on the results of distributing the questionnaire, it was found that there was an increase in partners' knowledge and skills regarding 3D printing as a learning medium from 15% to 90%.